Antigen and Transforming Growth Factor Beta Receptors Contribute to Long Term Functional and Phenotypic Heterogeneity of Memory CD8 T Cells - Hu, Yinghong; Cauley, Linda (Frontiers in Immunology, 2013)
Pathogen-specific CD8 T cells provide a mechanism for selectively eliminating host cells that are harboring intracellular pathogens. The pathogens are killed when lytic molecules are injected into the cytoplasm of the infected cells and begin an apoptotic cascade. Activated CD8 T cells also release large quantities of proinflammatory cytokines that stimulate other immune cells in the local vicinity. As the alveoli are extraordinarily sensitive to cytokine induced damage, multiple layers of immune regulation limit the activities of immune cells that enter the lungs. These mechanisms include receptor-mediated signaling pathways in CD8 T cells that respond to peptide antigens and transforming growth factor-beta. Both pathways influence the functional and phenotypic properties of long-lived CD8 T cells populations in peripheral and lymphoid tissues.